Kualitas Butir Soal Biologi Kelas X IPA MAN 1 Merangin Tahun Ajaran 2021/2022 - Devi Nurpitasari (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
Based on the information obtained from the Biology teacher at MAN 1 Merangin,the teacher has not analyzed the questions that have been used in the Final Semester Exam test for class X MAN 1 Merangin. This study aims to determine the quality of teacher-made Biology items for the 2021/2022 academic year based on validity, reliability, level of difficulty, discriminatory power, and effectiveness of distractors. This research approach uses descriptive quantitative research based on validity, reliability, level of difficulty, discriminating power and effectiveness of distractors. The validity of the items categorized as sufficient reaches 8% (2 items) the items are accepted. Reliability on questions that have a reliable index of 0.40 are in the low category. The level of difficulty in the questions in the medium category reaches 80% (20 items) the items are accepted. The differentiating power in the good category questions reached 8% (2 items), on the medium category questions it reached 64% (16 items) items were accepted. The effectiveness of distractors on the very good category found 12% (3 items), the good category items reached 44% (11 items) the items were accepted. The results showed that all questions had poor quality because they did not meet the standard criteria so that the questions were remade or revised. Keywords: Quality of items, Biology questions